Less Ado, More Done: Verbal and Visual Antithesis in the Media. - Hilde van Belle (Informal Logic, 2013)
The inventive, argumentative and stylistic possibilities generated by figures in general and the figure antithesis in particular are explored by Jeanne Fahnestock in the field of science. These ideas on the possibilities of antithesis are developed in the analysis of some cases of this figure in the media. This paper explores how antithesis can consist of textual and visual elements, and how various sorts and degrees of opposition are constructed in the figure.